Building integration of active solar energy systems: A review of geometrical and architectural characteristics - Vassiliades, C.; Agathokleous, Rafaela; Barone, G.; Forzano, Cesare; Giuzio, G.F.; Palombo, Adolfo; Buonomano, Annamaria; Kalogirou, Soteris A. (My University, 2022)
Solar building integration, differs from everyday active solar energy systems on a building envelope, because the active system replaces building elements and are integrated into the architectural envelope and structure. This article aims to present a comprehensive review and analyse the geometrical and architectural characteristics and design possibilities offered by the building integration of active solar energy systems. The literature studies are separated into double and single façade solutions, as well as solutions where the active system performs as an independent architectural element of the building. It is concluded that the majority of the researchers preferred the single façade solutions, followed by the double façade systems since the second one offers a cavity which can be used as an air duct for the BIPV (Building Integrated Photovoltaics) and BIPV/T (Building Integrated Photovoltaic/Thermal) solutions. This work provides an overview of the state of the art systems and geometrical solutions emerging by the development, research, and applications of the BISS (Building Integrated Solar Systems).
Keywords: Active solar energy systems; Building integration; BIPV; BIPV/T; BISTS